Maize grain yield and water use efficiency in relation to climatic factors and plant population in northern China - Yue-e LIU; Peng HOU; Gui-rong HUANG; Xiu-li ZHONG; Hao-ru LI; Jiu-ran ZHAO; Shao-kun LI; Xu-rong MEI (Journal of Integrative Agriculture, 2021)
Water scarcity has become a limiting factor for increasing crop production. Finding ways to improve water use efficiency (WUE) has become an urgent task for Chinese agriculture. To understand the response of different maize populations to changes in precipitation and the effects of changes in maize populations on WUE, this study conducted maize population experiments using maize hybrids with different plant types (compact and semi compact) and different planting densities at 25 locations across China. It was found that, as precipitation increased across different locations, maize grain yield first increased and then decreased, while WUE decreased significantly. Analyzing the relationship between WUE and the main climatic factors, this study found that WUE was significantly and negatively correlated with precipitation ($$ (daily mean precipitation) and R (accumulated precipitation)) and was positively correlated with temperature (TM (daily mean maximum temperature), TM–m (Tm, daily mean minimum temperature) and GDD (growing degree days)) and solar radiation ($$ (daily mean solar radiation) and Ra (accumulated solar radiation)) over different growth periods. Significant differences in maize grain yield, WUE and precipitation were found at different planting densities. The population densities were ranked as follows according to maize grain yield and WUE based on the multi-site experiment data: 60 000 plants ha–1 (P2)>90 000 plants ha–1 (P3)>30 000 plants ha–1 (P1). Further analysis showed that, as maize population increased, water consumption increased significantly while soil evaporation decreased significantly. Significant differences were found between the WUE of ZD958 (compact type) and that of LD981 (semi-compact type), as well as among the WUE values at different planting densities. In addition, choosing the optimum hybrid and planting density increased WUE by 21.70 and 14.92%, respectively, which showed that the hybrid played a more significant role than the planting density in improving WUE. Therefore, choosing drought-resistant hybrids could be more effective than increasing the planting density to increase maize grain yield and WUE in northern China. Comprehensive consideration of climatic impacts, drought-resistant hybrids (e.g., ZD958) and planting density (e.g., 60 000 plants ha–1) is an effective way to increase maize grain yield and WUE across different regions of China.